Institutional Considerations in Strengthening On-farm Client-Oriented Research in National Agricultural Research Systems: Lessons from a Nine-Country Study - Merrill-Sands, Deborah; Biggs, Stephen D.; Bingen, R. James; Ewell, Peter T. (Cambridge University Press, 1991)
Many national research systems have launched major on-farm research efforts aimed at generating relevant technologies for resource-poor farmers, but institutional and policy factors have often hindered the effectiveness of these efforts. Experience has shown that on-farm research, linking farmers, researchers, and technology transfer agents, poses special organizational and managerial challenges. Institutional innovations and strong policy commitment are needed if on-farm research is to succeed in meeting the needs of resource-poor farmers. Sound research methods alone are not sufficient.This paper reviews key policy, organizational and managerial considerations for integrating on-farm client-oriented research as an effective and stable component of national agricultural research systems. It summarizes the findings of a major study sponsored by the International Service for National Agricultural Research on institutional factors affecting the performance and sustainability of such research systems. The conclusions are based on the systematic analysis of over 25 discrete on-farm research efforts in nine developing countries. The objective is to provide research managers, on-farm researchers and on-farm research advisors with concrete and practical insights for strengthening on-farm research and its contribution to the generation and transfer of relevant technologies.Integración de la investigación de granja con los sistemas nacionales